2022
DOI: 10.5194/acp-22-11239-2022
|View full text |Cite
|
Sign up to set email alerts
|

Chemical evolution of secondary organic aerosol tracers during high-PM2.5 episodes at a suburban site in Hong Kong over 4 months of continuous measurement

Abstract: Abstract. Secondary organic aerosol (SOA) makes a sizable contribution to fine-particulate-matter (PM2.5) pollution, especially during high-PM episodes. Past studies of SOA evolution at the episode scale mainly rely on measurements of bulk SOA mass, with few studies probing individual SOA molecular tracers. In this study, we continuously monitored (at a bi-hourly resolution) SOA tracers specific to a few common volatile organic compound (VOC) precursors at a suburban site in Hong Kong for a 4-month period from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Recent studies reported O 3 mixing ratios of more than 100 ppb in Guangdong-Hong Kong urban area. 7,92 Hundreds of O 3 pollution days exceeding O 3 levels over 100 ppb were also observed in Shanghai metropolitan area. 93 These increasing O 3 levels in the ambient air in China will certainly have implications on O 3 reactivity within indoor environments, where we spent most of our time.…”
Section: Indoor Air Implicationsmentioning
confidence: 88%
“…Recent studies reported O 3 mixing ratios of more than 100 ppb in Guangdong-Hong Kong urban area. 7,92 Hundreds of O 3 pollution days exceeding O 3 levels over 100 ppb were also observed in Shanghai metropolitan area. 93 These increasing O 3 levels in the ambient air in China will certainly have implications on O 3 reactivity within indoor environments, where we spent most of our time.…”
Section: Indoor Air Implicationsmentioning
confidence: 88%
“…The sampling site is ∼5–10 km away from the nearby urban commercial centers and surrounded by residential neighborhoods, with relatively low influences of local anthropogenic sources except for a construction site and small student canteen, which is representative of a clean suburban environment in Hong Kong. For a detailed description of the sampling site, we refer readers to our recent work (Wang et al., 2022a). The monitored parameters include hourly PM 2.5 , its major chemical composition, and molecular and elemental markers, as well as the meteorological parameters.…”
Section: Methodsmentioning
confidence: 99%
“…All the mentioned online data at even hours were chosen to match the TAG-measured data and used for further analysis. The SHARP PM 2.5 and RH data were corrected due to the measurement bias, see more discussion in Wang et al (2022a) and Text S1 in Supporting Information S1. Details of the data validation and quality assessment are provided in Text S2 in Supporting Information S1.…”
Section: Sample Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The commercial thermal‐desorption aerosol GC‐MS has recently been used for hourly observations of organic molecular markers (OMMs) in eastern China (X. He et al., 2020; R. Li et al., 2020; Q. Wang et al., 2022). The observational results provide valuable information on the sources and evolution of primary and secondary organic aerosols (SOA) during pollution episodes.…”
Section: Introductionmentioning
confidence: 99%